Terpenes from Marine-Derived Fungi - Ebel, Rainer (Molecular Diversity Preservation International, 2010)
Terpenes from marine-derived fungi show a pronounced degree of structural diversity, and due to their interesting biological and pharmacological properties many of them have aroused interest from synthetic chemists and the pharmaceutical industry alike. The aim of this paper is to give an overview of the structural diversity of terpenes from marine-derived fungi, highlighting individual examples of chemical structures and placing them in a context of other terpenes of fungal origin. Wherever possible, information regarding the biological activity is presented.